EDUCATION AND THE NATION STATE: AN ANALYSIS OF PHILIPPINE PRESIDENTIAL SPEECHES - ANCHO, INERO VALBUENA; CALIMBAHIN, GENEVIE-ABI M.; RIVERA, JAESSER; TINA, JANREY C. (Jurnal Studi Pemerintahan, 2020)
How do Philippine Presidents present issues on education in their presidential speeches? What are pertinent concerns in education sector that are identified and given attention during the speech? How do these issues relate to the overall approach of the address? As a qualitative study, this paper utilizes data gathered from online repositories, as transcripts of presidential speeches delivered through the State of the National Address (SONA) are available online. These materials include those delivered by President Arroyo, President Aquino, and President Duterte. The narrative of President Arroyo’s SONA weaves economy and education. Strengthening the economy through strategic management and sound policies has been instrumental in achieving quality education. It is also strongly evident how the thrust of President Aquino in education is shown in his first three consecutive years of reports to the people. Various changes, huge or small still matter for they made significant propulsion and advancement in the quality of education for Filipinos. President Duterte’s administration showcases preventive measures on crime, violence, and drugs by means of devising programs and laws for the eventual attainment of universal quality education.